2016
DOI: 10.1021/jacs.6b11337
|View full text |Cite
|
Sign up to set email alerts
|

Redox Active Ion-Paired Excited States Undergo Dynamic Electron Transfer

Abstract: Ion-pair interactions between a cationic ruthenium complex, [Ru(dtb)(dea)][PF], C1 where dea is 4,4'-diethanolamide-2,2'-bipyridine and dtb is 4,4'-di-tert-butyl-2,2'-bipyridine, and chloride, bromide, and iodide are reported. A remarkable result is that a 1:1 iodide:excited-state ion-pair, [C1, I], underwent diffusional electron-transfer oxidation of iodide that did not occur when ion-pairing was absent. The ion-pair equilibrium constants ranged 10-10 M in CHCN and decreased in the order Cl > Br > I. The ion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 60 publications
6
76
0
Order By: Relevance
“…Quantum yields of 0.60-0.70 were calculated for all R-SA À derivatives. These cage escape yields are signicantly larger than those found in the diffusional excited-state electrontransfer oxidation of iodide by ruthenium excited states (<0.10) 66,72 and larger than ion-pairs formed between iodide and ruthenium polypyridyl complexes with cape yields of 0.34 73 and 0.25-0.50. 21 For PCET in hydrogen-bonded systems, Ø CE is oen not measured, or irrelevant because the products never dissociate.…”
Section: Proton-coupled Electron Transfer Excited-state Quenchingmentioning
confidence: 65%
See 1 more Smart Citation
“…Quantum yields of 0.60-0.70 were calculated for all R-SA À derivatives. These cage escape yields are signicantly larger than those found in the diffusional excited-state electrontransfer oxidation of iodide by ruthenium excited states (<0.10) 66,72 and larger than ion-pairs formed between iodide and ruthenium polypyridyl complexes with cape yields of 0.34 73 and 0.25-0.50. 21 For PCET in hydrogen-bonded systems, Ø CE is oen not measured, or irrelevant because the products never dissociate.…”
Section: Proton-coupled Electron Transfer Excited-state Quenchingmentioning
confidence: 65%
“…Due to the complexity of charge distribution in the ruthenium complexes and salicylate derivatives, developing a reasonably accurate approximation for the electrostatic work terms is difficult. 46,73,81,82 However, within a single ruthenium complex, such as Ru-Bpz, these work terms are not be expected to vary signicantly, and as such we chose to model solely the Ru-Bpz data as it provided the largest uniform series, Fig. 10A.…”
Section: Mechanistic Discussionmentioning
confidence: 99%
“…Such bimolecular chemistry, and others in general, involves diffusion of the A and the D to form an encounter complex prior to electron transfer (11,36). The freeenergy change associated with the encounter complex formation is small in polar solvents, but becomes more significant in low dielectric media (37). If coupling within the encounter complex is strong at the instance of electron transfer, an adiabatic pathway may be operative that is expected to decrease the yield of products from that calculated based on formal reduction potentials.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the roles that intermolecular interactions have in mediating electron transfer are very challenging to define. During the last two decades, a body of literature has shown that electrostatic interactions 9 , 10 , hydrogen bonding 11 13 , and other non-bonding interactions 14 19 can enhance IET rates, but interactions that are too strong may suppress reactivity by lowering the driving force for reaction 20 . This scenario provides the imperative to understand how weak intermolecular interactions can increase IET rates without compromising chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%